2008
DOI: 10.1021/ac801053g
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Human Plasma 1H NMR Spectroscopic Data Processing for High-Throughput Metabolic Phenotyping Studies and Detection of Insulin Resistance Related to Type 2 Diabetes

Abstract: Optimizing NMR experimental parameters for high-throughput metabolic phenotyping requires careful examination of the total biochemical information obtainable from (1)H NMR data, which includes concentration and molecular dynamics information. Here we have applied two different types of mathematical transformation (calculation of the first derivative of the NMR spectrum and Gaussian shaping of the free-induction decay) to attenuate broad spectral features from macromolecules and enhance the signals of small mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 40 publications
0
51
0
Order By: Relevance
“…3). The plasma metabolite assignment generally needs at least two 1D NMR experiments [18]: a pulse-and-acquire sequence, in which large signals of macromolecules preclude small molecules analysis, and a transverse relaxation-edited sequence (also called a Carr-Purcell-Meiboom-Gill (CPMG)) in which small molecules are observed due to the suppression of signals from protons with short T 2 relaxation times. The signal of both types of components can be detected in only one step with the DOSY-ES experiment.…”
Section: Application To Natural or Biological Mediummentioning
confidence: 99%
“…3). The plasma metabolite assignment generally needs at least two 1D NMR experiments [18]: a pulse-and-acquire sequence, in which large signals of macromolecules preclude small molecules analysis, and a transverse relaxation-edited sequence (also called a Carr-Purcell-Meiboom-Gill (CPMG)) in which small molecules are observed due to the suppression of signals from protons with short T 2 relaxation times. The signal of both types of components can be detected in only one step with the DOSY-ES experiment.…”
Section: Application To Natural or Biological Mediummentioning
confidence: 99%
“…Recently, metabonomics has been applied to the evaluate DM-and DN-related diseases (9,17,18,32,33). These studies suggested potential markers of DM-and DN-related diseases, such as the nonesterified fatty acids and esterified fatty acids, lipids, acyl-carnitines, acyl-glycines, and metabolites related to tryptophan metabolism.…”
mentioning
confidence: 99%
“…A number of papers dealing with statistical 2D covariance analysis have recently appeared in the field of NMR spectroscopy, notably by BrĂŒschweiler [102][103][104][105][106], Nicholson [108][109][110][111][112][113][114][115][116] and others [117][118][119][120][121]. For example, Chen et al [102] reported that 2D NMR spectra can be generated by the covariance approach by using a relatively few t 1 increments.…”
Section: Covariance and Correlation Coefficient Mappingmentioning
confidence: 99%
“…Johnson et al [112] used the kinetic variant of STOCSY called J-resolved STOCSY to study acyl glucuronide intra-molecular transacylation reaction. Maher et al [113] applied STOCSY for high-throughput metabolic phenotyping for diabetes detection. Lindon et al [114] claimed STOCSY is related to samplesample correlation in the review of NMR application on metabonomics.…”
Section: Covariance and Correlation Coefficient Mappingmentioning
confidence: 99%